The H1 haplotype of the endothelial protein C receptor protects against arterial thrombosis in patients with antiphospholipid syndrome. Issue 169 (September 2018) - Plasín-Rodríguez, Miguel Angel; Rodríguez-Pintó, Ignasi; Patricio, Patricia; Monteagudo, Joan; Cervera, Ricard; Reverter, Joan Carles; Espinosa, Gerard; Tàssies, Dolors
Abstract: Introduction: Genetic variants in the endothelial protein C receptor gene ( PROCR ) may contribute to the thrombosis risk by regulating levels of the soluble form of this protein (sEPCR). We evaluated whether PROCR polymorphisms and sEPCR levels play a role in the thrombotic manifestations of antiphospholipid syndrome. Materials and methods: One hundred and seventy-five patients (62 with primary antiphospholipid syndrome, 30 with antiphospholipid syndrome associated with systemic lupus erythematosus, 40 with systemic lupus erythematosus without antiphospholipid antibodies and 43 with systemic lupus erythematosus and antiphospholipid antibodies) and 66 healthy controls were included. PROCR H1 and H3 haplotypes were determined by genotyping 7014G/C and 1651C/G tag-polymorphisms, respectively. sEPCR levels were determined by enzyme-linked immunosorbent assay. Results: PROCR haplotype distribution was similar among groups of patients and controls. PROCR H1 and H3 haplotypes were less prevalent in antiphospholipid syndrome patients with arterial thrombosis than those without arterial thrombosis, but statistical significance was only reached for the H1 haplotype (58.0% vs. 85.7%, p = 0.003; odds ratio: 0.23 [95% CI 0.08–0.65]). No relationship between the PROCR H1 and H3 haplotypes and venous thrombosis was found. sEPCR levels were higher in H3 than in H1 carriers (175.5 [95% CI 60.9–290.1] ng/ml vs. 69.1 [95% CI 61.5–76.9] ng/ml, p < 0.01). No relationship of sEPCR with arterial or venous thrombosis was found. Conclusion: The PROCR H1 haplotype was less frequently found in APS patients with arterial thrombosis, suggesting a protective effect of PROCR H1 against arterial thrombosis in these patients. No relationship between sEPCR and thrombosis was found. Highlights: APS patients with arterial thrombosis had a lower prevalence of PROCR H1 haplotype. PROCR H1 could have a protective role against arterial thrombosis in APS. No association was found between thrombosis and PROCR H3 haplotype or sEPCR. sEPCR levels were higher in PROCR H3 than in PROCR H1 carriers.